AZERBAIJAN AND THE INTERNATIONAL CRIMINAL COURT: NAVIGATING CHALLENGES AND SEIZING OPPORTUNITIES - Zhi-Zhuang, Mehriban (American Journal of Legal Practice (AJLP), 2023)
This article explores the implementation of the Statute of the International Criminal Court in the national legislation of the Republic of Azerbaijan. Through a comparative analysis of the national legislation of foreign countries, the article provides insights into the advantages and disadvantages of the ICC’s Statute in the implementation of national legislation. The paper examines the activities of the International Criminal Court and analyses its complementary jurisdiction, the execution of an order, criminal offences and international crimes. Recommendations and conclusions from the policies of both jurisdictions are presented. This article provides valuable insights into the challenges and opportunities that arise when implementing international law into national legal systems